'Everything About Being Indie Is All Tied to Not Being Black': Indie Music, Race, and Identity in Medicine for Melancholy and Pariah. Issue 2 (1st December 2022) - SEXTON, JAMIE
Abstract : In this article I will explore the use of indie music within two African American independent films, Medicine for Melancholy (2008) and Pariah (2011). These two films are rare examples of African American films featuring an extensive employment of indie music, despite a huge growth in such music appearing within feature films over the past twenty years. I investigate some of the racial contours of indie music and examine how it is utilised within the two films under analysis. Both these films employ indie music to explore individuals who do not conform to some of the more stereotypical characteristics of black identities. I frame these analyses within a broader discussion of the links between indie music – particularly indie rock – and whiteness, exploring prejudices against, and marginalisation of, many black music artists within indie music cultures.